KHARKIV SCHOOL OF FOREST TYPOLOGY, ITS SIGNIFICANCE IN THE MODERN EDUCATIONAL PROCESS - Pozniakova, Svitlana (Sworld-Us Conference proceedings, 2023)
The work examines the formation and development of the Kharkiv School of Forest Typology, the founders of which were professors D.V. Vorobyov, B.F. Ostapenko The scientific school of forest typology is of great importance in the training of forestry speci